Penerapan Pembelajaran Kooperatif Teknik Two Stay Two Stray Berbasis Praktikum Untuk Meningkatkan Minat Belajar Dan Prestasi Belajar Siswa Dalam Pembelajaran Fisika Di SMP - Subagja, Erik Adi (2015)
This research is about the application of cooperative learning techniques two stay two stray based practicum to increase interest and junior high student achievement. Background on this issue one of which is less precise learning methods used to cause a lowering interest in student learning so that students have difficulties in learning physics. One way to overcome these problems is the need for the implementation of cooperative learning techniques two stay two stray based practicum that can facilitate students actively participate in learning activities. The purpose of this study was to analyze the effect of the application of cooperative learning techniques two stay two strau based practicum increase interest and achievement of junior high school students learn physics. The method used by the researchers is Quasi-experimental design with Nonequivalent Control Group Design. The subjects in this study were students of class VIII A as an experimental class and class VIII C as Appellant, both located in the SMP 26 Bandung. The selection of the sample is purposive sampling. These results are an increase in student achievement, this is shown by the results of the test post-test of 67.56. This result is greater than the average score of the pre-test of 42.00. In addition, the increased influence of cooperative learning techniques two stay two stray based practicum better than learning interactive lectures. This is evident from the experimental class of normalized gain value is 0.44. While the class of normalized gain value comparison is 0.30. Cooperative learning techniques two stay two stray based practicum also can improve students' interest in learning physics. This is shown by the average percentage of post-test score results by 75.09%. This result is greater than the average percentage of the pre-test score of 49.37%.